Unmet needs for hypertension diagnosis among older adults in Myanmar: secondary analysis of a multistage sampling study - Ikuma Nozaki; Yugo Shobugawa; Yuri Sasaki; Daisuke Takagi; Yuiko Nagamine; Poe Ei Zin; Thae Zarchi Bo; Than Win Nyunt; Min Zaw Oo; Kay Thi Lwin; Hla Hla Win (BMC, 2022)
Abstract Background Hypertension is a major cause of morbidity among older adults. We investigated older adults' access to health services in Myanmar by focusing on unmet needs in diagnosing hypertension. This study aims to identify factors associated with the unmet needs for hypertension diagnosis in the study areas of Myanmar. Methods This is a secondary data analysis of the survey which is a cross-sectional study conducted with older adults (aged ≥ 60 years) in the Yangon and Bago regions of Myanmar. Objective indicators of health were collected, including blood pressure, height and weight. The diagnosis of hypertension was considered an unmet need when a participant's blood pressure measurement met the diagnostic criteria for hypertension but the disease had not yet been diagnosed. Bivariate and multivariate analyses using logistic regression were performed to identify factors associated with the unmet need for hypertension diagnosis. Factors related to lifestyle habits and medical-seeking behaviour were selected and put into the multivariate model. Results Data from 1200 people, 600 from each of the two regions, were analysed. Altogether 483 (40.3%) participants were male, 530 (44.2%) were aged ≥ 70 years, and 857 were diagnosed with hypertension based on their measured blood pressure or diagnostic history, or both, which is a 71.4% prevalence of hypertension. Moreover, 240 (20.0%) participants had never been diagnosed with hypertension. In the multivariate analysis, these unmet needs for hypertension diagnosis were significantly associated with male sex (odds ratio [OR] 1.46, 95% confidence interval [CI] 1.05-2.05), residence in the Bago region (OR 1.64, 95% CI 1.09-2.45) and better self-rated health (OR 1.70, 95% CI 1.24-2.33), but not with education, category on the wealth index or living arrangement. Conclusions There are barriers to accessing health services for hypertension diagnosis, as evidenced by the regional disparities found in this study, and charitable clinics may decrease the financial barrier to this diagnosis.